CALCULATION OF RIGID PAVEMENT MACAN DAHAN ROAD CONSTRUCTION PROJECT LINGGANG BIGUNG DISTRICT WEST KUTAI - RUNG, LI (KURVA S JURNAL MAHASISWA, 2014)
Highway infrastructure development is the process of opening the trafficspace that aims to overcome the various barriers of geography, which in thisprocess, basically involves the transfer and deformation of the earth's surface ortopography. Historical development of roads has been started since the firsthumans inhabit the earth, where they attempt to first find a way to find and fulfilltheir needs, especially food.At this time the development of transport infrastructure is a top priority, asit aims to open up isolated areas and spur economic growth in rural communitiesin particular. One example is the construction of Jalan Tigers Dahan in SubLinggang Bigung.West Kutai is the result of the division of Kutai, has undergone manysignificant changes, both in terms of area due to the expansion and developmentof existing infrastructure. These changes, of course continue to encourage andstimulate the Government of West Kutai today, to continue to develop the existingpotential of the region in realizing a just society, and prosperous appropriate.To achieve these objectives, the Government of West Kutai District continues toencourage the achievement of equitable development, in order to spur economicgrowth and development of the region. Salasatu kinds of activities are activitiesTigers Wicker Road Development In Sub Linggang Bigung which is the localgovernment efforts in improving transportation infrastructure, particularly forland transport in the District Linggang Bigung, West Kutai.The planning process that is well planned and organized, and supported bya team of professional, experienced, solid and reliable in accordance with thefield work is handled, will be able to produce a quality product technical planningand appropriate, so that the targets that have been programmed can be executedwith good and careful.To support this, the construction of roads that exist in Jalan Tigers Dahanin District Linggang Bigung, requires careful technical planning, developmentprocess in accordance with the quality of time and cost, as well as directionalcontrol processes.